Trends in Michigan Farmers’ Information Seeking Behaviors and Perspectives on the Delivery of Information - Murari Suvedi; Shelly Campo; Maria Knight Lapinski (Journal of Applied Communications, 1999)
A sample of Michigan farmers was surveyed in 1996 and 1999 to examine trends in their information-seeking behaviors and preferred methods of information delivery. In addition, the relationship between demographic characteristics and types of information sources used were examined. Some key findings for both years include: (a) The vast majority of farmers do not use web-based information; (b) income and farm size was positively correlated with all types of information delivery (print, web-based, radio/TV, organizational events and personal sources); and (c) part-time farmers and those with outside employment tended to use fewer information sources than full-time farmers. Suggestions are offered to help educators make better choices in campaign and message delivery.